Structural characteristics of the core layer and biomimetic model of the ladybug forewing. (October 2017) - Chen, Jinxiang; Xu, Mengye; Okabe, Yoji; Guo, Zhensheng; Yu, Xindi
Graphical abstract: Highlights: There are trabeculae existing in the frame of the ladybug ( H. axyridis ) forewing. It was the first time to propose the parameters, N, the total number of trabeculae and λt, the ratio of the cross-sectional area of them to a forewing. The cross sectional area of a single trabecula is the smallest and its trabecular density is the highest, as high as 84 per square millimeter. The λt values of H. axyridis, A. dichotoma and P. inclinatus are about 1.0%, 1.5% and 10.5%, respectively, and the N values are all above 1000. A biomimetic model of the ladybug forewing with a high-density distribution of thin trabeculae and a foam-like material in the core layer is firstly proposed. Abstract: To explore the characteristics of the core structure of ladybug ( Harmonia axyridis ) forewings, their microstructure was studied using microscopes. The results suggest that trabeculae exist in the frame of the beetle (ladybug) forewing for the first time; this study represents the first determination of the parameters N, the total number of trabeculae in each forewing, and λt, the ratio of the cross-sectional area of the trabeculae to the effective area of trabecular distribution. The cross-sectional area of a single trabecula in the ladybug forewing is smaller than those in two other kinds of beetles, Allomyrina dichotoma and Prosopocoilus inclinatus . However, the average trabecular density of the ladybug forewing is 84 per square millimeter, which is the highest among these three kinds of beetles. The λt values are 1.0%, 1.5% and 10.5% for H. axyridis, A. dichotoma and P. inclinatus, respectively, and the corresponding N values are approximately 1.4, 1.7 and 3.7 thousand, respectively. Based on these findings, a biomimetic model of the ladybug forewing is proposed, which is characterized by a core structure with a high-density distribution of thin trabeculae surrounded by a foam-like material.